European organizations and the governance of ethnocultural diversity after the Cold War: The Yugoslav "laboratory" - Caplan, R (Taylor and Francis, 2014)
The post-Cold War period to date has witnessed renewed international and especially European preoccupation with issues pertaining to ethnocultural diversity and the challenges for governance arising from these issues. This article discusses the shift that has occurred in support of national minority rights in Europe and why European organizations have become more concerned with these rights after the Cold War. It examines some of the major policy initiatives adopted by European organizations in response to the nearly 25-year long Yugoslav crisis and what these initiatives reveal about new (and old) thinking within these organizations with respect to national minority rights and the management of ethnocultural diversity more generally. It also discusses the consequences of these initiatives for minority rights protection and some of their broader implications for European policy in the future. © 2014 Taylor & Francis Group, LLC.